English in the Connemara Gaeltacht: A Sociophonetic Study of Bilingual and Monolingual Speakers - Tallon, Kate (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2025)
This thesis presents a sociophonetic investigation of Connemara English, comparing the English of 12 native Irish speakers with that of 12 monolingual English speakers. It addresses a research gap in the study of Irish English (IrE) in using quantitative methods to examine cross-linguistic (Irish and English) and cross-varietal (English dialects) variation among the bilinguals and monolinguals. The English spoken by native Irish speakers has been commonly characterised as a variety heavily influenced by Irish (e.g. Ó hÚrdail, 1997), with some scholars proposing that such influences are due to linguistic transfer from these speakers' L1 Irish. This creates a distinction between L1 Irish influences and historical substratal Irish influences reported for monolingual IrE varieties (Kallen, 1985). The Connemara Gaeltacht was chosen for two reasons. Firstly, the English varieties therein have not yet been quantitatively documented. Secondly, the opportunity to study present-day language contact between Irish and English in this area is diminishing due to the rapid decline of Irish. The primary aim of this study is to provide an empirical description of the following features: PEN-PIN merger, FACE and GOAT variation, liquid+sonorant epenthesis (e.g. in `film'), /t/-variation, and /l/-variation. It examines, in the first place, whether the English of native Irish speakers exhibits L1 influence from Irish and whether their English differs (in line with the above features) from that of monolinguals from the same region. The secondary aim is to question the extent to which a synchronic study of Gaeltacht English and reported ongoing language contact processes can shed light on historical language contact between Irish and English. Speech data in Irish and English (read sentences and interviews) and social data (age, gender, attachment to community, language dominance and use) were collected from the 24 speakers. This data was acoustically and statistically analysed to explore the relationship between phonetic variation and linguistic and social factors. The results indicate that bilingual and monolingual speakers of Connemara English significantly differ in their realisation of these IrE features. However, these differences vary with age; while older monolingual and bilingual speakers exhibit considerable divergence from one another, their younger counterparts display similar speech patterns. The results indicate an ongoing change in progress in Connemara English. For bilingual speakers, the lack of parallels in Irish for certain features call for a recharacterisation of Gaeltacht English as a variety that is not one-dimensionally synchronically influenced by L1 Irish but is perhaps conservative toward older IrE speech patterns, which may show either Irish substratal traces or retentions from older British English input varieties. It is concluded that a consideration of synchronic variation in these speakers is limited in elucidating past language contact processes between Irish and English. There are many social and sociohistorical factors that complexify this task. Overall, this study makes important contributions to the fields of Irish English linguistics by questioning past descriptions of Gaeltacht English and advancing the understanding of present-day language contact and variation in the Connemara Gaeltacht through quantitative sociophonetic analysis.
APPROVED
Keywords: Irish English; language contact; Gaeltacht; phonetics; sociophonetics; bilingualism; language variation and change